Juicily juxtaposed - Lunaček, Izar T. (Teorija in praksa, 2016)
The article argues for the ninth art as the most suitable medium for an artistically and critically engaged depiction of human sexuality, and demonstrates its point with a historical tour of the genre from Tijuana bibles through American superhero and horror comics to the US underground, European mastery and, finally, Moore and Gebby's 21st century meta-porn masterpiece, Lost girls. The article enriches this historical tour with meditations on the relation between erotica and pornography, the funny and serious, and fantasy and reality in the sex life of humans.
Keywords: Comic books, strips, etc.; Erotica; Erotika; Pornografija; Pornography; spolno življenje; Stripi